Exploration of spectra of periodic Comet 153P/Ikeya−Zhang - Churyumov, K.I.; Lukyanyk, I.V.; Chubko, L.S.; Kleshchonok, V.V.; Berezhnoy, A.A.; Chavushyan, V.H.; Sandoval, L.; Palma, A. (Кинематика и физика небесных тел, 2005)
We present preliminary results of study of middle-resolution optical spectra of Comet 153P/Ikeya–Zhang obtained on May 5, 2002 with the help of the 2.12-m reflector of the Guillermo Haro Astrophysical Observatory. Emission lines of the molecules C₂, C₃, CN, NH₂, CO (Asundi and triplet bands), and H₂O⁺ are identified in these spectra. On the basis of the intensity distribution along the slit of the spectrograph in C₂, C₃, CN emission lines we determined the velocities expansion and life times of these molecules.